Cardiovascular health supervision for Duchenne Muscular Dystrophy; data from the MD STARnet. (March 2018) - Wittlieb-Weber, Carol A.; Pantea, Cristian; Krikov, Sergey; Westfield, Christina; Fox, Deborah J.; Pandya, Shree; Bounsanga, Jerry; Johnson, Nicholas E.; Butterfield, Russell J.; Venkatesh, Y. Swamy; Ciafaloni, Emma
Abstract: Background: In 2005, the American Academy of Pediatrics (AAP) published a policy statement on cardiovascular health supervision for Duchenne Muscular Dystrophy (DMD). Data is lacking on its effect on cardiovascular care. Methods: Using the infrastructure of the Muscular Dystrophy Surveillance, Tracking and Research Network, we examined a population-based sample of individuals with DMD, focusing on cardiac testing and prescription of cardiac medication. Comparisons were made pre- (2000–2005) and post- (2006–2011) publication Results: 731 cases were studied; mean age of diagnosis 3.8 years and mean duration of follow-up 9.3 years. There was a significant decrease in time from diagnosis to first electrocardiogram (ECG) and echocardiogram (ECHO) from pre- to post-publication; 1047 (95% CI: 905–1188) days to 411 (95% CI: 324–498) days for ECG ( p  < 0.01) and 1153 (95% CI: 1022–1284) days to 352 (95% CI: 280–424) days for ECHO ( p  < 0.01). Only 4.5% and 8.2% of those ≥10 years of age met the recommendation for yearly ECG and ECHO respectively. Prescription of a cardiac medication with an abnormal ECHO increased post-publication 91/125, 72.8% versus pre- 47/77, 61.0% ( p  = 0.08). After 2005, cases with a normal ECHO were 2.3 (95% CI 1.23–4.31) times more likely to be prescribed a cardiac medication ( p  < 0.01). Conclusions: Since publication of the AAP statement, DMD patients are having cardiac testing sooner and cardiac medication is prescribed more often. However, the majority are not having testing with recommended frequency. Overcoming barriers to recommended cardiac care may lead to a better understanding of the natural history of cardiomyopathy in DMD and better treatment strategies. Highlights: There has been a significant decrease in time from DMD diagnosis to cardiac testing. Males with DMD are getting cardiac testing at a younger age. Cardiac medications are being prescribed more often to boys with DMD. Frequency of cardiac testing for boys with DMD does not meet published guidelines.